Negotiation as a means of developing and implementing environmental policy - Charles C. Caldart; Nicholas Askounes Ashford (Fondazione Eni Enrico Mattei (FEEM), 1998)
In the environmental area, negotiated rulemaking, implementation, and compliance are proposed by their advocates as delivering two primary benefits: reduced rulemaking time and decreased litigation over a final agency rule. The experience to date, however, indicates that negotiated rulemaking cannot be relied upon to deliver either of these benefits. Nonetheless, experience indicates that negotiation can, in appropriate circumstances, facilitate a better understanding of issues, concerns, facts, and positions among adversaries, promote the sharing of relevant information, and provide an opportunity for creative problem-solving. This paper examines three negotiated rulemakings by the U.S. Environmental Protection Agency (EPA) under the Clean Air Act. The three negotiations are evaluated according to whether negotiation was instrumental either in securing a more protective standard, or in securing an innovative technological response. It also addresses a fourth type of policy-relevant negotiation – known as regulatory reinvention – wherein the agency has assembled groups of interested parties to focus on regulatory issues concerning a particular industry sector, with an eye toward developing "cleaner, cheaper, smarter" ways of reducing or preventing pollution. The three examples studied here indicate that, in situations in which a strong or dramatic regulatory signal is necessary to produce the desired technological response, negotiated rulemaking is not likely to be advisable. Since negotiated rulemaking relies on consensus, and since the regulated industry is unlikely to agree to a regulatory standard that it perceives as having a dramatic effect, negotiated rulemaking is unlikely to creative the incentive necessary to spur innovation. However, where the desired technological change is likely to come more easily, appropriate use of negotiated rulemaking may help facilitate an innovative technological response. Negotiation would appear to work best as a means of securing improved health, safety, or environmental outcomes in situations in which the necessary regulatory signals for improvement and innovation are already in place. This is a primary reason that EPA's Supplemental Environmental Project (SEP) policy has been relatively successful at securing pollution prevention and other environmental benefits as a part of the negotiation of settlement agreements with non-compliant companies. It also suggests that the agency could also encourage meaningful technological change through a more creative and aggressive use of its authority to grant innovation waivers to selected companies at the implementation stage. Moreover, it is a primary reason why EPA's regulatory reinvention strategy has, thus far, failed to live up to expectations.
Keywords: D74; I18; J28; J52; K32; L50; O31; O38; 330; Alternative dispute resolution; Environment; Environmental negotiation; Environmental regulation; Negotiated compliance; Negotiated implementation; Negotiated regulation; Negotiated settlement; Negotiation; Regulation; Technological change; Technological innovation; Umweltpolitik; Verhandlungstheorie; USA